Analisis Faktor-Faktor Yang Berdampak Terhadap Kualitas Laporan Keuangan Pada Lembaga Perkreditan Desa - Anak Agung Putu Gede Bagus Arie Susandya; I Ketut Sunarwijaya (Journal of Innovative and Creativity, 2025)
Financial reports serve as the final output of accounting processes and play an important role in providing financial information to stakeholders. This study investigates the influence of human resource competence, accounting understanding, information technology utilization, supervisory body functions, and leadership ethics on the quality of financial reports at Village Credit Institutions (LPDs) in Denpasar City. Using a sample of 73 employees selected through purposive sampling and analyzed with multiple linear regression, the findings reveal that human resource competence, accounting understanding, information technology utilization, and leadership ethics positively affect financial report quality. However, the supervisory body function shows no significant effect on the quality of financial reports.